Spirituality and Religiosity During the Peri-Operative Period for Cancer Patients and their Family: An Integrative Systematic Review - Joann B. Hunsberger; M. Jennifer Cheng; Rebecca A. Aslakson (Palliative Medicine and Hospice Care, 2014)
Background: Religion and Spirituality (R/S) may influence cancer patient’s emotional distress, mental health and healing throughout their diagnosis and treatment. Objective: This systematic review examines studies exploring R/S of cancer patients and their family in the perioperative period. Design: We completed a systematic review of the databases MEDLINE, EMBASE, CINAHL, SCOPUS, the Web of Science, and Cochrane library concerning the terms “religion and spirituality” and “cancer surgery”. Inclusion criteria included qualitative or quantitative studies evaluating R/S of cancer patients or their family members within the perioperative period (one month pre- and post-surgery). Exclusion criteria included review articles, grey literature, editorials, case studies and studies evaluating R/S of healthcare providers. Results: Seven publications met criteria for analysis. Five studies described cross-sectional surveys, one used a focus-group approach, and one utilized in-person interviews. Studied popu-lations predominantly were female breast cancer patients. There were considerable heterogene-ity in survey instruments, variables, and outcomes. Based on these studies: 1) Faith and religious beliefs were used as coping mechanisms during the perioperative period; 2) Evangelical Christians tended to differ in religious coping compared to Catholics; 3) R/S correlated with coping styles and distress; 4) There was increased religious coping and religious involvement during the perioperative period; Conclusions: Studies evaluating R/S of cancer patients and their families in the perioperative period are few and heterogeneous in design. Direct comparison is difficult, but data suggests that R/S during the perioperative period may increase as compared to R/S during other stages of cancer diagnosis and treatment.